Financial inclusion, agricultural inputs use, and household food security evidence from Nigeria - Balana, Bedru; Olanrewaju, Opeyemi (International Food Policy Research Institute, 2024)
This paper examines the effects of financial inclusion on adoption and intensity of use of agricultural inputs and household welfare indicators using data from the nationally representative Nigerian LSMS wave-3 (2015/2016) survey. For this, we constructed a financial inclusion index from four formal financial services access indicators (bank account, access to credit, insurance coverage, and digital transaction) using multiple correspondence analysis (MCA). We used Cragg’s two-step hurdle, instrumental variables for binary response variables, and a Generalized Method of Moments (GMM) models in the econometric analysis. Results show that households with access to formal financial services are more likely to adopt agricultural inputs and to apply these more intensively. These same households are less likely to experience severe food insecurity and are more likely to consume diverse food items. We also find that these effects are less for female farmers regardless of formal financial inclusion, suggesting that they may bear more non-financial constraints than their male counterparts. The results suggest a need for targeted interventions to increase access to formal financial services of farm households and gender-responsive interventions to address the differential constraints women farmers face.